Energetics of B-to-Z transition in DNA. - Peck, L J (1983)
Analysis by two-dimensional gel electrophoresis of topoisomers of plasmids containing d(pCpG)n . d(pCpG)n inserts, in which n ranges between 8 and 21, shows that the B-to-Z transition within the alternating C-G is readily induced by negative supercoiling and is highly cooperative. The free energy parameters for the transition in dilute aqueous buffers have been evaluated from a statistical mechanical analysis of the data, and these parameters allow prediction of the superhelicities of plasmids at which the transition occurs in alternating C-G inserts over a wide range of lengths. In agreement with the crystal structures, the helical handedness of the B structure in solution and that of the Z structure are shown to be opposite to each other. Furthermore, it is found that the B form of the alternating C-G sequence in solution has a helical periodicity of 10.5 +/- 0.1 base pairs per turn, and the Z form has a helical periodicity of 11.6 +/- 0.3 base pairs per turn. There also appears to be a significant unwinding of the right-handed DNA duplex at each of the B/Z junctions.